The semantics of makan ‘to eat’ in Malay / Mufidah Mohamed - Mufidah , Mohamed (2020)
This study will explore and explain the cognitive semantics of makan ‘to eat’ in Malay, as there are various usages of makan ‘to eat’ that do not only denote their literal senses, but also metaphorical meanings such as makan hati (lit: to eat one’s heart) ‘to get offended’ and makan tuan (lit: to eat an owner) ‘to be betrayed’. The data will be collected from authentic texts which are online news articles, published novels, books and magazines. The data will be explained using Conceptual Blending Theory (Fauconnier & Turner, 1998, 2002) to demonstrate the mechanism of meaning constructions between two input spaces. Moreover, by employing CBT, the study will justify reasons for all the expressions containing the word makan ‘to eat’. Also, when necessary, sociocultural aspects will be explored. However, the results cannot be generalised as the data collected are from selected and limited sources only. The findings show that the usages of the word makan ‘to eat’ can be grouped into literal, semi-literal and extensions that consist of endocentric, partial-endocentric and exocentric (for compounds). Some metaphorical usages of makan ‘to eat’ were used in form of phrases